Intermediate Algebra (12th Edition)

Published by Pearson
ISBN 10: 0321969359
ISBN 13: 978-0-32196-935-4

Chapter 4 - Section 4.1 - Integer Exponents and Scientific Notation - 4.1 Exercises - Page 278: 117



Work Step by Step

Using the laws of exponents, the given expression, $ (5a^{-1})^4(a^2)^{-3} ,$ is equivalent to \begin{array}{l}\require{cancel} 5^4a^{-1(4)}(a^{2(-3)}) \\\\= 5^4a^{-4}(a^{-6}) \\\\= 5^4a^{-4+(-6)} \\\\= 5^4a^{-4-6} \\\\= 5^4a^{-10} \\\\= \dfrac{5^4}{a^{10}} \\\\= \dfrac{625}{a^{10}} .\end{array}
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.